The Effect of Digital Noise Reduction on Annoyance and Speech Perception in Low and High Acceptable Noise Level Groups - Hemanth Narayan Shetty; Navya Bilijagalemole Nanjundaswamy (International Archives of Otorhinolaryngology, 2019)
Abstract